Effect of Accelerator Addition on the Drying Time, Thickness and Glossy Clear Coat in Vehicle’s Body - Muhamad Fajar Sidiq; Sultanul Reza Islami; M. Agus Shidiq (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
Painting is the application of paint in liquid form onto the object, to create a thin layer which is then dried to form a hard layer or layers of paint. Many things are influential in the painting process, including the clear coat process which functions as a gloss effect and protects and maintains the paint color of the vehicle. In this research, it was expected to know the effect of the ratio between the thinner and accelerator on the clear coat on drying time, thickness, and glossiness of the clear coat. In this study, the mixture ratio variations of accelerator and thinner used were 0%: 100%, 25%: 75%, 50%: 50%, 75%: 25%. The speeds of drying with the aforementioned ratio of accelerator and thinner were 28 mins, 24 mins, 18 mins, and 16 mins respectively, while the values of the thickness of the ratio were 53, 4 µm, 55.6 µm, 54.03 µm, and 57.1 µm respectively, and the glossiness values of the accelerator and thinner with the ratio were 96.1 Gu, 95.4 Gu, 92.5 Gu, and 93.1 Gu respectively.